Automatic landmark annotation in 3D surface scans of skulls: Methodological proposal and reliability study. (October 2021) - Bermejo, Enrique; Taniguchi, Kei; Ogawa, Yoshinori; Martos, Rubén; Valsecchi, Andrea; Mesejo, Pablo; Ibáñez, Oscar; Imaizumi, Kazuhiko
Highlights: Automatic approach for the annotation of standardized craniometric landmarks. Hybrid method: template-based initialization and knowledge-based refinement of landmark coordinates. Reliability study for 58 landmarks over 30 surface scans of male adult skulls. Inter and intra-observer analysis performed by three experts shows high variability. Performance of the automatic method is comparable to manual landmarking. Abstract: Background and Objectives: Craniometric landmarks are essential in many biomedical applications, such as morphometric analysis or forensic identification. The process of locating landmarks is usually a manual and slow task, highly influenced by fatigue, skills and the experience of the practitioner. Localization errors are propagated and magnified in subsequent steps, which can result in incorrect measurements or assumptions. Thereby, standardization, reliability and reproducibility lay the foundations for the necessary accuracy in subsequent measurements or anatomical analysis. In this paper, we present an automatic method to annotate 3D surface skull models taking into account anatomical and geometrical features. Methods: The proposed method follows a hybrid structure where a deformable template is used to initialize the landmark positions. Then, a refinement stage is applied using prior anatomical knowledge to ensure a correct placement. Our proposal is validated over thirty 3D skull scans of male Caucasians, acquired by hand-held surface scanning, and a set of 58 craniometric landmarks. A statistical analysis was carried out to analyze the inter- and intra-observer variability of manual annotations and the automatic results, along with a visual assessment of the final results. Results: Inter-observer errors show significant differences, which are reflected in the expert consensus used as reference. The average localization error was 2.19 ± 1.5 mm when comparing the automatic landmarks to the reference location. The subsequent visual analysis confirmed the reliability of the refinement method for most landmarks. Conclusions: Repeated manual annotations show a high variability depending on both skills and expertise of the observer, and landmarks' location and characteristics. In contrast, the automatic method provides an accurate, robust and reproducible alternative to the tedious and error-prone task of manual landmarking.